2007
DOI: 10.1029/2006jd008114
|View full text |Cite
|
Sign up to set email alerts
|

Levoglucosan levels at background sites in Europe for assessing the impact of biomass combustion on the European aerosol background

Abstract: [1] Atmospheric levoglucosan has been determined as a proxy for ''biomass smoke'' in samples from six background stations on a west-east transect extending from the Atlantic (Azores) to the mid-European background site KPZ (K-Puszta, Hungary). Concentration levels of levoglucosan (biannual averages) in the west-east transect range from 0.005 mg/m 3 at the oceanic background site AZO (Azores) to 0.52 mg/m 3 at AVE (Aveiro, Portugal). The atmospheric concentration of ''biomass smoke'' (biannual averages) was der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
352
6
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(408 citation statements)
references
References 53 publications
42
352
6
2
Order By: Relevance
“…This is in accordance with Puxbaum et al (2007), who concluded that biomass smoke is the predominant organic aerosol constituent in the winter in mid and Western Europe. These authors also found that, from all of the studied locations, the Portuguese site was the one registering the most pronounced seasonality in the contribution of biomass burning to PM levels, with the highest concentrations in the winter and the lowest in the summer.…”
Section: Discussionsupporting
confidence: 79%
“…This is in accordance with Puxbaum et al (2007), who concluded that biomass smoke is the predominant organic aerosol constituent in the winter in mid and Western Europe. These authors also found that, from all of the studied locations, the Portuguese site was the one registering the most pronounced seasonality in the contribution of biomass burning to PM levels, with the highest concentrations in the winter and the lowest in the summer.…”
Section: Discussionsupporting
confidence: 79%
“…Our results demonstrate that the blood pressure effect of BC observed in the United States and Europe (30,31) is not limited to high-income countries where BC is primarily from motor vehicles, although residential biomass combustion contributes to winter ambient air pollution in northern climates (32)(33)(34). The stronger health effect of BC from roadway exposure or combined roadway-biomass exposure may also be an important environmental risk factor for cardiovascular diseases in developing countries like China where the number of motor vehicles is rapidly increasing and household use of biomass and coal fuels persists (5,35).…”
Section: Discussionmentioning
confidence: 93%
“…Previously monitoring data from a background area which has not been contaminated by certain preponderant source emissions are often used to assess the source apportionment of the regional pollution (Puxbaum et al, 2007;Wang et al, 2014;Zhang et al, 2010). In this work, total suspended particulate (TSP) and fine particulate matter (PM 2.5 ) samples were collected in summer, 2013 at the Yellow River Delta, North China.…”
Section: Introductionmentioning
confidence: 99%